1990
DOI: 10.1143/jjap.29.l984
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of Quasi-Bookshelf Layer Structure in New Ferroelectric Liquid Crystals Derived from a Naphthalene Ring

Abstract: A quasi-bookshelf layer structure has been obtained by a conventional rubbing method at room temperature in a FLC mixture composed of naphthalene-derived liquid crystals. This layer structure is spontaneously formed due to a unique temperature dependence of the interlayer spacing; X-ray diffraction indicates that the layer spacing decreases from 34 to 33.5 Å and then increases to 33.8 Å with decreasing temperature in SmC*. Contrary to the unusual behavior of the layer spacing, the director tilt angle determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Recently, it has been found that there exist a number of smectic C * materials with different molecular structure (see, for example, Refs. [4,[6][7][8][9]) with anomalously weak layer contraction in the SmC phase. In fact, different materials are characterized by varying the degree of contraction below the SmA−SmC phase transition, and the majority of SmC liquid crystals correspond to the intermediate cases between strong and anomalously weak layer contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that there exist a number of smectic C * materials with different molecular structure (see, for example, Refs. [4,[6][7][8][9]) with anomalously weak layer contraction in the SmC phase. In fact, different materials are characterized by varying the degree of contraction below the SmA−SmC phase transition, and the majority of SmC liquid crystals correspond to the intermediate cases between strong and anomalously weak layer contraction.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of the smectic layer spacing with lowering temperature not only in SmC Ã A but also in SmC Ã has been observed in several compounds and mixtures, although detailed study has not been carried out as yet. [47][48][49][50][51][52][53][54] This means that the relative displacements of molecules along their long axes or the layer undulational fluctuations as the pretransitional effect may play an important role in the temperature variation of the smectic layer spacing. In other words, we can insist on the importance of the other transition from SmC Ã /SmC Ã A to the hexatic or crystalline phase than the one from SmA to SmC Ã /SmC Ã A .…”
Section: Liquid Crystals 873mentioning
confidence: 99%
“…A possible solution for this problem can be liquid crystalline materials with a de Vries-type phase transition, in which the transition happens with a negligible layer shrinkage. [14][15][16] In recent years, several such liquid crystalline materials have been reported, some of which contain a siloxane backbone.…”
Section: -6mentioning
confidence: 99%